A study to estimate similarities or dissimilarities of thyroid parameters of cord blood and new-born venous blood amongst new-borns - Gangalam, Vamsi K.; Vodapally, Deepika (International Journal of Contemporary Pediatrics, 2021)
Background: Hypothyroidism may be congenital or may be acquired which might or may not have a delayed onset. Incomplete thyroid development and decreased thyroid hormone biosynthesis is a result of congenital hypothyroidism. Screening is usually missed in areas where testing is not done and being the reason for new cases of hypothyroid cases. The aim was to assess/evaluate whether cord blood can be used as a primary screening method for congenital hypothyroidism. Methods: The study was taken up in the department of pediatrics of a tertiary teaching hospital. A total of 200 babies were taken for the study during the whole study period. The cord blood at the time of delivery and 48 hour serum blood was collected and sent to the lab for thyroid profile estimation. Results: The study consisted of 109 males and 91 female infants. Among the 200 subjects, 156 were term babies and 44 preterm. The mean birth weight was 2.44 kgs. The mean cord TSH was 6.89±4.56, the mean T3 level was 81.03±38.84 and mean T4 level among the subjects was 11.17±3.33. The capillary venous blood was collected after 48 hours for thyroid profiling. The mean TSH was 5.15±3.13, mean T3 level was 111.53±36.49 and mean T4 level was 14.65±6.07. On comparison of cord blood and venous blood association was noted between them. Conclusions: From the present study findings it can be suggested cord blood can be used as a marker for early detection of congenital hypothyroidism.